2015
DOI: 10.1002/open.201500206
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Dependent Facile Synthesis of Diaryl Selenides and Biphenols Employing Selenium Dioxide

Abstract: Biphenols are important structure motifs for ligand systems in organic catalysis and are therefore included in the category of so‐called “privileged ligands”. We have developed a new synthetic pathway to construct these structures by the use of selenium dioxide, a stable, powerful, and commercially available oxidizer. Our new, and easy to perform protocol gives rise to biphenols and diaryl selenides depending on the solvent employed. Oxidative treatment of phenols in acetic acid yields the corresponding biphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Next, we optimized the ratios of phenolic components 1 and 2 with respect to the yield and selectivity. Previous studies indicated that the oxidation of 1 is more facile than that of 2 . Thus, we decided to use component 1 in excess amount relative to the amount of phenol 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we optimized the ratios of phenolic components 1 and 2 with respect to the yield and selectivity. Previous studies indicated that the oxidation of 1 is more facile than that of 2 . Thus, we decided to use component 1 in excess amount relative to the amount of phenol 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is an excellent oxidizer for scientific and industrial applications. Recently, we reported the first selective oxidative homocoupling of phenols by using selenium dioxide as the oxidizer . In that study, the solvent turned out to be crucial for the transformation to obtain selectively either the diaryl selenides or the 2,2′‐biphenols.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium dioxide (SeO 2 ) is often used as oxidizing agent or catalyst in organic chemistry, [94][95][96][97] but very seldom used for the synthesis of organoselenium compounds. [98,99] Few reported works using SeO 2 are, synthesis of diarylselenides from arylboronic acids, [100] biphenols from phenols, [101] α-selenoamidation of aryl methyl ketones. [102] Subsequently, Zhou et al, [103] developed an environmentally benign, metal-free efficient synthetic protocol resulting in selenylation of electron rich anilines 38 and phenylimidazo[1,2-a]pyridines 39.…”
Section: Selenofunctionalization Of Carbocyclic Heterocyclic and Unsmentioning
confidence: 99%
“…Most commonly, methods based on transition-metal catalysis, 5,6 or stoichiometric and over stoichiometric amounts of oxidants are used. [6][7][8] However, these strategies suffer from several disadvantages: Many of the reagents applied are costly and/or toxic. 8 Additionally, a significant amount of reagent waste is created, which subsequently has to be disposed or recycled laboriously.…”
mentioning
confidence: 99%
“…[6][7][8] However, these strategies suffer from several disadvantages: Many of the reagents applied are costly and/or toxic. 8 Additionally, a significant amount of reagent waste is created, which subsequently has to be disposed or recycled laboriously. Facing a rising need in sustainability as one of the largest global challenges, the methods mentioned above are not contemporary and appropriate anymore.…”
mentioning
confidence: 99%